Pre-pregnancy community-based intervention for couples in Malaysia: application of intervention mapping. (December 2016) - Norris, Shane; Ho, Julius; Rashed, Aswir; Vinding, Vibeke; Skau, Jutta; Biesma, Regien; Aagaard-Hansen, Jens; Hanson, Mark; Matzen, Priya
Abstract Background Malaysia is experiencing a nutrition transition with burgeoning obesity, particularly in women, and a growing prevalence of non-communicable disease. These health burdens have severe implications not only for adult health but also across generations. Pre-conception health promotion could address the intergenerational risk of metabolic disease. This paper describes the development of the "Jom Mama" intervention using Intervention Mapping (IM). The Jom Mama intervention aims to improve the health of young adult couples in Malaysia prior to conception. Methods IM comprises of five steps prior to the last one, which involves the evaluation of the intervention. We used the five steps to develop the Jom Mama intervention. Results Both the process and evidence is documented providing the rationale to the selection of the key objectives of the intervention: (i) increasing healthy dietary practice; (ii) increasing physical activity levels, (iii) reducing sedentary activity; and (iv) improving social support to offset stressful lifestyles. From the IM process, Jom Mama will be health-system centred approach that uniquely combines both community health promoters and an electronic-health platform to deliver the complex intervention. Conclusion IM is an iterative process that systematically gathers "best" evidence, selects appropriate theories of behaviour change, and facilitates formative research so as to develop a complex intervention. Though the IM process is time consuming, complex, and costly, it has enriched the Jom Mama intervention with a number of notable advantages: (i) intervention fashioned on formative work with stakeholders and in the target group; (ii) intervention combines research evidence with theory; (iii) intervention acknowledges multiple dynamics of influence; and (iv) intervention is embedded within health service priorities in Malaysia for greater scale-up possibility.